GENDER PECULIARITIES OF ENGLISH PHRASEOLOGICAL UNITS (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This study investigates gender peculiarities in English phraseological units (PUs) to reveal how language encodes cultural attitudes, stereotypes, and social hierarchies related to masculinity and femininity. Phraseological units—idioms, fixed expressions, and proverbs—serve as linguistic markers of historically shaped gender concepts. Using cognitive, sociolinguistic, and semantic analysis, the study categorizes gender-marked idioms, examines their conceptual metaphors, and evaluates the extent of gender asymmetry. The findings indicate that male-related idioms predominantly highlight strength, rationality, and authority, whereas female-related idioms emphasize emotionality, beauty, domestic roles, or social dependence. Additionally, the article identifies modern trends toward gender neutrality and inclusive expression in contemporary English. The research concludes that while traditional idioms preserve historical gender biases, current linguistic changes reflect evolving cultural attitudes toward gender equality.